The regionalization of labour markets by modelling commuting behaviour - Frank Cörvers; Maud Hensen (European Regional Science Association (ERSA), 2003)
There hardly exists any country in which regional employment issues do not play an important role in economic planning or policy making. The need for models to carry out policy analyses in this field of research is evident. In order to analyse regional labour markets administratively defined areas are usually taken as units of analysis. On the one hand, labour market policies targeted on these administratively defined areas may be less effective if the administrative boundaries do not follow functionally linked labour market areas. On the other hand, it may be very difficult for local planning authorities to set policy goals with regard to another subdivision of areas than the administrative subdivision. Therefore it is important for policy makers at the regional level to be aware of the functional interdependencies between regions, in particular when these regions are not functional regional labour markets. In our paper we subdivide functional regional labour markets by modelling the commuting behaviour of workers in the Netherlands. For a better understanding of regional labour markets and their dynamics, commuting behaviour of workers is analysed by using the distance travelled from home to work (see Isserman et al., 1986). The commuting decision depends on workers' background characteristics like age, sex, education, income or region-specific variables. By analysing the impact of these determinants on commuting, we are able to compare the average commuter of a country, in our case the Netherlands, with the commuters at the municipality level. By taking a closer look at the commuters at the municipality level, we find municipalities in which commuters act significantly different from the average commuter. These differences in commuting behaviour at the municipality level give an impression of the relative labour market attractiveness of the municipalities and thereby of the ratio between labour demand and supply in regions. We use these differences in commuting behaviour to regionalize the labour market. Although many studies have analysed commuting behaviour, a regionalization of labour markets with respect to different groups of workers has rarely been made. In the paper commuting flows of different groups of workers are used to subdivide the national labour market into functional regional labour markets. Contrary to earlier research (for example Green et al. 1991), we prevent to use arbitrarily chosen cut-off points to regionalize the labour market. Instead, we model the commuting behaviour of individual workers and use statistical criteria to subdivide regional labour markets (see also Baumann et al. 1996). Moreover, we show that the resulting regionalization of the labour market strongly depends on the group of individual workers concerned in the analysis. For example, it is shown that workers travel on average 21,5 kilometres for the home-to-work journey and that this distance increases with the educational level of the commuters. Therefore the regional labour market for workers with a high level of education is relatively large. To perform our empirical analysis we use journey-to-work data from Statistics Netherlands (CBS, 2001).
Keywords: 330